2022
DOI: 10.1055/s-0042-1742352
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Transcutaneous Protheses – A Systematic Review of Publications Over the Past 10 Years

Abstract: Introduction Bone conduction implants, responsible for transmitting sound from an external processor to the inner ear, can be divided into active and passive, depending on the vibratory stimulus location. The use of transcutaneous device has increased, given its aesthetic appeal, the complications and limitations of percutaneous devices, and patient's treatment adherence, focusing mainly on efficacy. However, various complications are associated with the use of transcutaneous prosthesis, which can often be ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The only other commercially available device in this class is the Bonebridge (MEDEL). 1,2,10 In a systematic review and meta-analysis of 14 1 Limitations were noted in pooling results for metaanalysis. Due to the relative rarity of SSD compared with CMHL, FG could not be meaningfully pooled for SSD meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only other commercially available device in this class is the Bonebridge (MEDEL). 1,2,10 In a systematic review and meta-analysis of 14 1 Limitations were noted in pooling results for metaanalysis. Due to the relative rarity of SSD compared with CMHL, FG could not be meaningfully pooled for SSD meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Complications are an area of interest, as transcutaneous devices are traditionally accepted to have a lower overall risk of complications compared with percutaneous devices. 10 Souza et al performed a targeted systematic review of complications associated with the Bonebridge against other devices (Baha Attract and Sophono). This demonstrated a lower risk of device-specific complications with Bonebridge, and a minor and major complication rate of 6.1% and 5.7% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cosmetic concerns are one of the main reasons why transcutaneous devices are popular, since they maintain skin surface integrity. However, these devices are not free of complications (de Souza et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, the implantation is more complex than for percutaneous devices, which may result in greater surgical risk. Souza et al [3] in a systematic review of the safety of BCHDs compared the original percutaneous to the transcutaneous approach and found that fewer complications occurred with the transcutaneous approach, and the number of major events was significantly lower for active transcutaneous devices such as the BB.…”
Section: Introductionmentioning
confidence: 99%